PENCATATAN DAN PEMISAHAN DATA LOG PROXY SERVER KE DALAM DATABASE MENGGUNAKAN MODEL OTOMATA MESIN TURING DI STMIK PPKIA PRADNYA PARAMITA MALANG - Affandi, Luqman (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
Development of the Internet has brought a significant impact on human life. To share Internet resources and anticipated adverse effects and the convenience of Internet users is necessary to control Internet access. One of them is by installing a squid proxy server. To be able to help improve the ability of the proxy server can be done by analyzing the log proxy server, because the record contains a record of users Internet access. But to be able to do further analysis is necessary to re-record data on the proxy log into a database. This is caused by the proxy server log file is recorded in a text file squensial so hard to do an analysis of the data. Needed a method to read and analyze the log file and the method can be used is the Turing machine model of automata. Turing machine is a deterministic finite state machine that has two-way tape. Â In the process of recording into the database, performed the separation of the information contained in the proxy log files. Separation is performed by the analysis of the proxy log file will be used for various controls such as site access, and who has access and others. Such information can be poured into a website, so that individuals who use Internet resources in a network can mutually control each other. Key words: Listing, Proxy Server, automata, and proxy server log